International Security in the Multi-Polar World (Economic and Political Thought, 2013)
The article is an attempt to answer a question about the role of the Euro--Atlantic system in the multi-polar international order and whether it willbe able to guarantee peace and security. Will it be able to compete with thegrowing power of China, India, Russia and other emerging super-powers?The author advances a thesis that it is very difficult to answer the abovequestions today because the world is becoming more and more unpredictableand the dynamic of the occurring changes is unprecedented. Moreover, theworld is still involved in the financial and economic crisis and it is hard to saywhen it is going to finish and what consequences it is going to have for theUnited States, the European Union and other members of the contemporaryinternational relations.The author shows that a new, multi-polar and multi-civilizational worldorder is coming into existence today and the analysis of the years 1991–2010proves that the Atlantic Alliance was not prepared for the collapse of thebipolar system and the Soviet empire, which was believed to be the biggestthreat for international peace and security. Moreover, the author wonderswhether the renaissance of the Atlantic Alliance is possible and whether itcan play the same role in the 21st century as it used to play under the leadershipof the United States in the 20th century. He suggests that if the AtlanticAlliance manages to break the present deadlock, it will be a co-author of thenew multi-polar international order. However, if it fails, the world will finditself in a long period of chaos, conflicts and wars because for dozens of yearsChina or India will not be strong enough to create a new international peacefulorder without or with marginalized participation of the Atlantic Alliance.